Improvement in Turn-Off Loss of the Super Junction IGBT with Separated n-Buffer Layers - Ki Yeong Kim; Joo Seok Noh; Tae Young Yoon; Jang Hyun Kim (Micromachines, 2021)
In this study, we propose a super junction insulated-gate bipolar transistor (SJBT) with separated n-buffer layers to solve a relatively long time for carrier annihilation during turn-off. This proposition improves the turn-off characteristic while maintaining similar on-state characteristics and breakdown voltage. The electrical characteristics of the devices were simulated by using the Synopsys Sentaurus technology computer-aided design (TCAD) simulation tool, and we compared the conventional SJBT with SJBT with separated n-buffer layers. The simulation tool result shows that turn-off loss (Eoff) drops by about 7% when on-state voltage (Von) and breakdown voltage (BV) are similar. Von increases by about 0.5% and BV decreases by only about 0.8%.